Distress improves after mindfulness training for progressive MS: A pilot randomised trial. (August 2015) - Bogosian, A; Chadwick, P; Windgassen, S; Norton, S; McCrone, P; Mosweu, I; Silber, E; Moss-Morris, R
Background: Mindfulness-based interventions have been shown to effectively reduce anxiety, depression and pain in patients with chronic physical illnesses. Objectives: We assessed the potential effectiveness and cost-effectiveness of a specially adapted Skype distant-delivered mindfulness intervention, designed to reduce distress for people affected by primary and secondary progressive MS. Methods: Forty participants were randomly assigned to the eight-week intervention ( n = 19) or a waiting-list control group ( n = 21). Participants completed standardised questionnaires to measure mood, impact of MS and symptom severity, quality of life and service costs at baseline, post-intervention and three-month follow-up. Results: Distress scores were lower in the intervention group compared with the control group at post-intervention and follow-up ( p < 0.05), effect size −0.67 post-intervention and −0.97 at follow-up. Mean scores for pain, fatigue, anxiety, depression and impact of MS were reduced for the mindfulness group compared with control group at post-therapy and follow-up; effect sizes ranged from −0.27 to −0.99 post-intervention and −0.29 to −1.12 at follow-up. There were no differences in quality-adjusted life years, but an 87.4% probability that the intervention saves on service costs and improves outcome. Conclusions: A mindfulness intervention delivered through Skype video conferences appears accessible, feasible and potentially effective and cost-effective for people with progressive MS.